1992
DOI: 10.1177/001872679204501003
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of the Causes of Corporate Wrongdoing in the United States

Abstract: It has been argued that a firm's propensity to violate federal laws and regulations is related to firm size, diversity, financial pressures, and organizational structure and processes (Clinard & Yeager, 1980). The current paper tests these propositions using United States data from the Occupational Safety and Health Administration and the Environmental Protection Agency. The findings offer at best weak support for some of these propositions while strongly suggesting that most are invalid. The results have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 12 publications
7
81
0
1
Order By: Relevance
“…For instance, organisational behaviourists have studied processes of changing jobs, getting a promotion, being laid off, retiring, employee turnover (Allison, 1984;Darden, Hampton & Boatwright, 1987;Lee et al 1992;Sheridan, 1992;Fournier, 2000Fournier, , 2001. Organisational mortality (Staber, 1992;Chen & Lee, 1993), store durations (Star and Massel, 1981;Dekimpe & Morrison, 1991), franchised network survival (Shane, 1996(Shane, , 1998aShane & Spell, 1998b;Shane & Foo, 1999;Cliquet & Perrigot, 2002), stability of international joint ventures (Blodgett, 1992), predicting illegal corporate behaviour (Baucus & Near, 1991;Hill et al, 1992), cash management as a strategic resource (Russo, 1991), brand loyalty in marketing (Duwors & Haines, 1990), are also some of the management topics using survival analysis. Demographers have been interested in births, marriages, divorces, migration patterns and deaths (Pollard et al, 1981).…”
Section: The Principles Of Survival Analysismentioning
confidence: 99%
“…For instance, organisational behaviourists have studied processes of changing jobs, getting a promotion, being laid off, retiring, employee turnover (Allison, 1984;Darden, Hampton & Boatwright, 1987;Lee et al 1992;Sheridan, 1992;Fournier, 2000Fournier, , 2001. Organisational mortality (Staber, 1992;Chen & Lee, 1993), store durations (Star and Massel, 1981;Dekimpe & Morrison, 1991), franchised network survival (Shane, 1996(Shane, , 1998aShane & Spell, 1998b;Shane & Foo, 1999;Cliquet & Perrigot, 2002), stability of international joint ventures (Blodgett, 1992), predicting illegal corporate behaviour (Baucus & Near, 1991;Hill et al, 1992), cash management as a strategic resource (Russo, 1991), brand loyalty in marketing (Duwors & Haines, 1990), are also some of the management topics using survival analysis. Demographers have been interested in births, marriages, divorces, migration patterns and deaths (Pollard et al, 1981).…”
Section: The Principles Of Survival Analysismentioning
confidence: 99%
“…Similarly, Hill and his colleagues (Hill, Kelley, Agle, Hitt, & Hoskisson, 1992) analyzed data regarding violations of the Occupational Health and Safety laws and concluded that variables such as ®nancial strain, ®rm size, diversity, decentralization, and incentive systemsÐsome of these attributes that Fox ®nds precursors of anti-human activityÐ``are not particularly useful predictors of the incidence of corporate wrongdoing'' (pp. 1072±1073).…”
Section: Resultsmentioning
confidence: 99%
“…Cochran and Nigh (1987) found a relationship between corporate violations and poor financial performance prior to violating. Finally, Hill et al (1992) found no relationship between firms under financial strain and corporate wrongdoing. Several studies have tested the pressure/opportunity model and note its empirical inconsistencies (Daboub et al, 1995;Hill et al, 1992;Jones, 1997;Szwajkowski, 1986).…”
Section: Defining Organizational Misconductmentioning
confidence: 88%
“…However, this prevailing theoretical explanation of organizational misconduct has not held up particularly well under empirical scrutiny (Daboub et al, 1995;Hill et al, 1992;Jones, 1997;Szwajkowski, 1986).…”
Section: Introductionmentioning
confidence: 99%